2021
DOI: 10.3390/d13120654
|View full text |Cite
|
Sign up to set email alerts
|

Homogenized Phylogeographic Structure across the Indo-Burma Ranges of a Large Monoecious Fig, Ficus altissima Blume

Abstract: As well as bountiful natural resources, the Indo-Burma biodiversity hotspot features high rates of habitat destruction and fragmentation due to increasing human activity; however, most of the Indo-Burma species are poorly studied. The exploration of plants closely associated with human activity will further assist us to understand our influence in the context of the ongoing extinction events in the Anthropocene. This study, based on widely and intensively sampled F. altissima across Indo-Burma and the adjacent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 90 publications
1
6
0
Order By: Relevance
“…This differs with yucca moth ( Tegeticula yuccasella ), which revealed no significant genetic structure between populations sampled in the native and planted host ranges (Leebens‐Mack & Pellmyr, 2004). However, similar result was found in the host plant F. altissima at its planted range (Huang et al, 2021). This finding suggested that similar genetic structuring may be achieved in obligate mutualisms at their expansion ranges despite a different introduction history.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…This differs with yucca moth ( Tegeticula yuccasella ), which revealed no significant genetic structure between populations sampled in the native and planted host ranges (Leebens‐Mack & Pellmyr, 2004). However, similar result was found in the host plant F. altissima at its planted range (Huang et al, 2021). This finding suggested that similar genetic structuring may be achieved in obligate mutualisms at their expansion ranges despite a different introduction history.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, large gene flow in E. altissima is supported by a relatively low level of differentiation among native populations and no distinct genetic structure among populations revealed by STRUCTURE (Figure 4, Figure 5c). Missing phylogeographic structure of F. altissima across Indo‐Burma and south China again supports the long‐distance dispersal of E. altissima (Huang et al, 2021). Those characters together suggest that long‐distance dispersal of E. altissima facilitates it tracking the host's artificial range expansion.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…In addition, fruit-eating animals like birds, monkeys and bats etc. also play a role in fig seed dispersal [ 34 , 35 ]. Meanwhile, according to our observations, the large effective population size and relatively continuous distribution of F. hirta may further prevent the loss of novel alleles, and consequently maintain the gene flow and genetic diversity.…”
Section: Discussionmentioning
confidence: 99%